The Five Necessities and Their Impact on Islamic Endowments - Ali Atiya Ali Al-Rubaie (Journal of Scientific and Human Dimensions, 2026)
Islamic endowments (Waqf) constitute a fundamental pillar in the economic and social structure of Islamic societies, playing a pivotal role in the redistribution of wealth and the realization of social solidarity. However, this system faces a set of contemporary challenges in the modern era, necessitating a re-evaluation of its implementation mechanisms to fulfill the objectives (Maqasid) of Islamic Sharia.The research problem stems from questioning the nature of the relationship between the five essential necessities (preservation of religion, life, intellect, lineage, and wealth) as a supreme Maqasidi theory, and the Islamic Waqf system as one of the most important tools for achieving these objectives.This study aims to analyze the theoretical and practical impact of the five necessities on the concept and roles of Waqf, and how the Waqf system can be an effective instrument for preserving these essential principles to serve the interests of people. The study adopts the descriptive, analytical, and inductive method to elucidate the theoretical framework of the five necessities, followed by analyzing the role of Waqf in preserving each necessity individually.The study reached several key findings, most notably: the relationship between Waqf and the five necessities is a closely integrated one, with Waqf embodying the practical application of achieving these Sharia objectives. The results also showed that the Waqf system possesses sufficient flexibility to adapt to contemporary developments in order to preserve these necessities, provided there is adherence to the governing Sharia frameworks and jurisprudential principles. The research recommends developing the administrative and investment mechanisms of Waqf institutions to maximize their role in preserving the five essential principles, and directing a portion of Waqf resources towards contemporary projects that serve these objectives, such as supporting scientific research, mental health initiatives, and combating societal ills.
Keywords: Islamic Waqf (Endowment); The Five Necessities (Al-Daruriyyat al-Khams); Maqasid al-Sharia (Objectives of Islamic Law); Preservation; Islamic Economic System